2022
DOI: 10.1111/ecc.13557
|View full text |Cite
|
Sign up to set email alerts
|

‘We do need to keep some human touch’ Patient and clinician experiences of ovarian cancer follow‐up and the potential for an electronic patient‐reported outcome pathway: A qualitative interview study

Abstract: Objective: This study aimed to explore experiences of follow-up after treatment and views on an electronic patient-reported outcome (ePRO) pathway among ovarian cancer patients and clinicians.Methods: Semi-structured qualitative interviews were conducted with clinicians and patients previously treated for ovarian cancer. Interviews explored experiences of the current follow-up pathway, patients' needs and views on an ePRO pathway enabling patients to report symptoms online rather than attend clinic-based appoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The e lectronic P atient self- R eported outcomes to I mprove cancer M anagement and patient E xperiences (ePRIME) system was composed between 2016 and 2018 following robust information technology and development work [ 27 ]. Qualitative interviews with clinicians and women previously treated for OC were conducted in 2016–2017 to explore their views of current follow-up and the prospect of ePRO follow-up [ 28 ]. The resulting system and pathway (described below) informed by this preliminary work sits in-between PIFU and routine clinic visits [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The e lectronic P atient self- R eported outcomes to I mprove cancer M anagement and patient E xperiences (ePRIME) system was composed between 2016 and 2018 following robust information technology and development work [ 27 ]. Qualitative interviews with clinicians and women previously treated for OC were conducted in 2016–2017 to explore their views of current follow-up and the prospect of ePRO follow-up [ 28 ]. The resulting system and pathway (described below) informed by this preliminary work sits in-between PIFU and routine clinic visits [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative interviews with clinicians and women previously treated for OC were conducted in 2016–2017 to explore their views of current follow-up and the prospect of ePRO follow-up [ 28 ]. The resulting system and pathway (described below) informed by this preliminary work sits in-between PIFU and routine clinic visits [ 28 ]. The 12-month feasibility study recruited 24 women treated for OC [ 29 ] and showed high compliance with ePRO questionnaires and community bloods, fewer visits, more phone calls (as planned) and high patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%